Embrio Destinasi Wisata Religi Baru: Identifikasi Komponen 3A Berbasis Wisata Ziarah Desa Balun, Lamongan - Indra P P Salmon; Ismail I; Wahyu Eko Pujianto; Fitroh Nadyah (JURNAL ILMIAH SYI'AR, 2020)
This study aims to examine the readiness and feasibility of supporting components in the midst of the designation of the Balun Village as the Pancasila Village and the Religious Tourism District of Lamongan Regency. Cultural attractions offered are the Mbah Alun Graveyard Site and the value of pluralism of religious community life in Balun Village. The study used a qualitative method with a descriptive analytic and participatory rural appraisal (PRA) approach. Data collection techniques in the form of narratives sourced from several informants, secondary statistical data, and field documentation. The results of the study indicate that the readiness represented in component 3A, namely: Attractions, in the form of cultural attractions either physical or tangible (pilgrimage sites) and non-physical or intangible (values of pluralism of society / diversity and religious festivals) have been owned and run for decades; Accessibility in the form of distance to Balun Village from strategic points relatively close (2-5 km) and road infrastructure conditions, as well as; Amenities and additional supporting elements in the form of services and other supporting services available such as accommodation for tourists, restaurants and culinary centers, souvenir centers, transportation points and access close to the main road. Another development that needs to be done is improvement in terms of accessibility considering the opportunity of arrival at the Balun Village Pilgrimage Site jumped dramatically on certain religious holidays.